The single nucleotide polymorphism rs4986790 (c.896A>G) in the gene TLR4 as a protective factor in corona virus disease 2019 (COVID-19) - Zacher, Christoph; Schönfelder, Kristina; Rohn, Hana; Siffert, Winfried; Möhlendick, Birte (Frontiers in Immunology, 2024)
Several factors, such as hypertension and diabetes mellitus, are known to influence the course of coronavirus disease 2019 . However, there is currently little information on genetic markers that influence the severity of COVID-19. In this study, we specifically investigated the single nucleotide polymorphism (SNP) rs4986790 in the TLR4 gene to identify a universal marker for preclinical prediction of COVID-19 disease progression.We analyzed the influence of demographics, pre-existing conditions, inflammatory parameters at the time of hospitalization, and TLR4 rs4986790 genotype on the outcome of COVID-19 in a comprehensive cohort (N = 1570). We performed multivariable analysis to investigate the impact of each factor.We confirmed that younger patient age and absence of pre-existing conditions were protective factors against disease progression. Furthermore, when comparing patients with mild SARS-CoV-2 infection with patients who required hospitalization or intensive care or even died due to COVID-19, the AG/GG genotype of TLR4 rs4986790 was found to be a protective factor against COVID-19 disease progression (OR: 0.51, 95% CI: 0.34 -0.77, p = 0.001). In addition, we demonstrated that low levels of interleukin-6 (IL-6) and procalcitonin (PCT) had a favorable effect on COVID-19 disease severity.In the subsequent multivariable analysis, we confirmed the absence of cardiovascular disease, low levels of IL-6 and PCT, and TLR4 rs4986790 AG/GG genotypes as independent predictors of potential hospitalization and reduction of severe or fatal disease course.3In this study, we identified an additional genetic factor that may serve as an invariant predictor of COVID-19 outcome. The TLR4 rs4986790 AG/GG genotype reduced by half the risk of COVID-19 patients requiring hospitalization, intensive care or to have a fatal outcome. In addition, we were able to confirm the influence of previously known factors such as pre-existing conditions and inflammatory markers upon the onset of disease on the course of COVID-19. Based on these observations, we hereby provide another prognostic biomarker that could be used in routine diagnostics as a predictive factor for the severity of COVID-19 prior to SARS-CoV-2 infection.